Financial Distress as an Agency Problem: Evidence on Non-Monotonic and Substitute Discipline Effects of Leverage and Competition - Mehmet Uğur; Edna Maeyen Solomon; Ayaz Zeynalov (Prague University of Economics and Business, Faculty of International Relations (FIR), 2021)
This paper addresses two issues encountered in the empirical financial distress literature: a-theoretical treatment of leverage and product-market competition as predictors of financial distress hazard; and lack of attention to frailty as a potential source of bias in reported estimates. We address the first issue by postulating that financial distress is essentially a managerial effort problem, mitigated by leverage and product-market competition as substitute disciplining devices with non-monotonic effects. To address the second issue, we utilize a multi-level financial distress hazard model with frailty. Drawing on an unbalanced panel of 13,986 listed firms from 1992 - 2014, we report three novel findings: (i) the effect of leverage on financial distress hazard is inverted-U-shaped; (ii) the effect of the competition is U-shaped; and (iii) leverage and competition are substitute disciplining devices that mitigate each other's adverse effects on financial distress hazard. The predictive power of the proposed model is high, and the results remain strongly or moderately robust to various sensitivity checks.
Keywords: C23; C25; C41; G30; G33; 330; Financial distress; competition; leverage; hazard modelling